Germanium-on-silicon nitride waveguides for mid-infrared integrated photonics - Li, Wei (2017)
A germanium-based platform with a large core-clad index contrast, germanium-on-silicon nitride waveguide, is demonstrated at mid-infrared wavelength. Simulations are performed to verify the feasibility of this structure. This structure is realized by first bonding a silicon-nitride-deposited germanium-on-silicon donor wafer onto a silicon substrate wafer, followed by the layer transfer approach to obtain germanium-on-silicon nitride structure, which is scalable to all wafer sizes. The misfit dislocations which initially form along the interface between germanium/silicon can be removed by chemical mechanical polishing after layer transfer process resulting in a high-quality germanium layer. At the mid-infrared wavelength of 3.8 μm, the germanium-on-silicon nitride waveguide has a propagation loss of 3.35 ± 0.5 dB/cm and a bend loss of 0.14 ± 0.01 dB/bend for a radius of 5 μm for the transverse-electric mode.